Philosophical Aspects of Critical Pedagogy of Paulo Freire in the Context of Students’ Academic Integrity - Oksana Petinova; Olha Nesterova (Studia Warmińskie)
The topic of academic integrity and ethics and culture of behavior is recognized as relevant in various communities and the scientific community. Homo digital, possessing a high level of critical thinking, should become the model of personality in the new paradigm of education. In the article, the authors analyze the philosophical aspects of Paulo Freire's critical pedagogy through the prism of academic integrity in the context of the modern development of the philosophy of education. They conclude that education is a means of liberating a person, and academic integrity is a way to achieve the same goal. Academic integrity is indirectly supported by the correct choice of communication methods, as well as procedures for creating new knowledge and the image of the world, which is personalized by a specific student. Various practices involved in the processes of perception allow a multidimensional understanding of the realities of the world. The authors emphasize that the concept of education, developed by the Brazilian pedagogue and philosopher F. Freire, involves a highly personal perception of the real world and educational content through a critical approach, which is supported by comparing the new knowledge acquired by the student with personal life experience.